Perancangan Atraksi dalam Pengembangan Desa Kendan Sebagai Desa Wisata di Kabupaten Bandung - Efanie Olivia Azmi; Dally Nur Arif; Dias Pratami Putri (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Kendan rural tourism, located in Nagreg District, Bandung Regency, is one of the attractive tourist destinations in the region. With its status as one of 50 tourist villages newly inaugurated by the Bandung Regency Culture and Tourism Office. This research aims to further develop the promotion and dissemination of information about the Kendan Tourism Village so that more people know and are interested in visiting. Descriptive research method with a qualitative research approach. The results of this Kendan rural tourism research show that the role of Stakeholders in the development of the Kendan Tourism Village. This research has identified the role of Stakeholders in the development of the Kendan rural tourism by applying the pentahelix model to identify the involvement and authority of each party. Designing tourist attractions for Kendan rural tourism. This research has succeeded in designing a comprehensive tourist itinerary for Kendan Tourism Village, which includes various attractions and activities that reflect the uniqueness and cultural characteristics of Kendan rural tourism.